Multi-core boron catalyst based on Si-O-Si framework bridging as well as preparation method and application of multi-core boron catalyst
By developing a catalyst based on the Si-O-SI Skeleton Bridge Liannuclear Boron Catalyst, the problem of harsh and selective reaction conditions in the polymerization reaction in the polymerization reaction was solved, and the low-carbon polymer was achieved. The characteristics of environmental protection.
Patent Information
- Application Number
- CN202411462410.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-05
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-24
AI Technical Summary
In the ring-opening polymerization and copolymerization reactions, existing catalysts are limited by the harsh reaction conditions and low product selectivity, making it difficult to effectively catalyze the preparation of low-carbon polymers.
A type of catalyst based on Si-O-Si skeleton bridged polynuclear boron was developed. This type of catalyst was prepared through hydroboration reaction. The synergistic effect of polyboron centers was used to improve the catalytic activity, and the catalytic performance was optimized by regulating the topology and reaction conditions.
A catalytic polymerization reactions with high efficiency and selectivity are achieved, and diverse low -carbon polymers are prepared, such as polyether, polyester, and polycarbonate, and the catalyst can be recycled. The process economy is effective and environmentally friendly.
Smart Images

Figure CN119350626A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalyst synthesis, and specifically relates to a Si-O-Si skeleton-bridged multi-nuclear boron catalyst and a preparation method and application thereof. Background Art
[0002] Si-O-Si as a catalyst framework has the following unique advantages in catalysis due to its unique structural and chemical properties: (1) Structural stability and flexibility: Si-O-Si bonds provide a stable and flexible framework that can withstand harsh reaction conditions without significant degradation. This robustness makes it suitable for a wide range of catalytic applications. (2) Adjustable porosity: The pore properties of the Si-O-Si framework can be easily adjusted by changing the synthesis conditions. This adjustability allows the optimization of pore size and volume, which is critical for accommodating a variety of reactants and products, thereby improving catalytic efficiency and selectivity. (3) High surface area: Materials based on the Si-O-Si framework, such as mesoporous silica, exhibit high surface area. This feature is advantageous for catalysis because it maximizes the contact between the catalytic sites and the reactants, potentially increasing reaction rates and yields. (4) Functionalization potential: The Si-O-Si framework provides a versatile platform that can be functionalized with a wide range of organic and inorganic groups. This adaptability enables the design of catalysts with active sites tailored for specific reactions, enhancing catalytic activity and selectivity. (5) Acid-base properties: The inherent acid-base properties of the Si-O-Si framework can be utilized in a variety of acid or base catalytic reactions. In addition, these properties can be further modified by post-synthesis treatment or incorporation of other elements, expanding the scope of catalytic applications. (6) Environmental friendliness: Silicon-based materials are generally considered to be environmentally benign. The use of catalysts based on the Si-O-Si framework is in line with the principles of green chemistry and can effectively reduce or eliminate the generation of hazardous substances. The unique combination of stability, tunability, and functionalization capabilities of the Si-O-Si framework makes it an outstanding candidate for use as a catalyst framework. Therefore, the development of catalysts containing the Si-O-Si framework has functions that other frameworks cannot achieve and provides the possibility of enhanced performance in a wide range of catalytic processes.
[0003] Organic boron catalysts are widely used in ring-opening polymerization and copolymerization to prepare low-carbon polymers, but organic boron based on Si-O-Si skeletons is rarely reported. The present invention provides a class of Si-O-Si skeleton-bridged multi-nuclear boron catalysts, which are applied to polymerization reactions to develop an economical, environmentally friendly, and catalyst-recyclable polymerization process. Summary of the invention
[0004] The application of existing catalysts in ring-opening polymerization (ROP) and ring-opening copolymerization (ROCOP) is often limited by harsh reaction conditions and low product selectivity. Catalysts based on Si-O-Si skeletons are expected to overcome these problems due to their unique physical and chemical properties. The object of the present invention is to propose a class of Si-O-Si skeleton-bridged multinuclear boron catalysts (abbreviated as multinuclear boron catalysts) and their preparation methods and applications. The disclosed Si-O-Si skeleton-bridged multinuclear boron catalyst system has the advantages of high activity and easy availability, can be used in the field of catalytic polymerization with high efficiency and selectivity, realizes the preparation of organic-inorganic hybrid boron catalysts, and greatly expands the types and application fields of organic boron catalysts.
[0005] The Si-O-Si skeleton-based bridged multi-nuclear boron catalyst of the present invention has a variety of topological structures, and the Si-O-Si skeleton can be a linear structure of Si-O-Si, a ring structure of Si-O-Si, or a cage structure of Si-O-Si. The feasibility of multiple topological structures gives the synthesis of multi-nuclear boron controllability. The Si-O-Si skeleton-bridged multi-nuclear boron catalyst can be efficiently prepared by a hydroboration reaction with a Si-O-Si skeleton containing a double bond (a Si-O-Si precursor compound containing a vinyl group). The multiple Lewis acid centers of this type of system can play a role in better activating monomers and stabilizing active species, reflecting the synergistic effect of the multi-boron center. The stability of the skeleton gives the catalyst a high temperature resistance. The multi-nuclear boron catalyst of the present invention is mainly used for preparing a variety of low-carbon polymers in ring-opening polymerization and copolymerization, such as polyethers, polyesters, polycarbonates, etc. In addition, after the polymerization reaction stops, the Si-O-Si polynuclear boron system (based on Si-O-Si skeleton-bridged polynuclear boron catalyst) is separated and recovered from the polymer, and the next polymerization reaction can be carried out while maintaining the catalytic activity before recovery. Moreover, through recycling, the polymerization process can achieve the goals of being economical, environmentally friendly and sustainable.
[0006] In the first aspect, the present invention provides a Si-O-Si skeleton-bridged multi-nuclear boron catalyst, the structure of which is shown below:
[0007]
[0008] Wherein, BY2 is independently selected from optionally substituted R1 is independently selected from hydrogen, halogen, optionally substituted straight or branched C1-8 alkyl, C1-8 alkoxy, C1-C8 alkenyl or C1-C8 alkynyl, optionally substituted aromatic, condensed aromatic or C3-C8 heterocyclic group; preferably, R1 is preferably C1-3 alkyl, phenyl; wherein, optionally substituted straight or branched C1-8 alkyl, C1-8 alkoxy, C1-C8 alkenyl or C1-C8 alkynyl, optionally substituted aromatic, condensed aromatic or C3-C8 heterocyclic group; The substituents in the aromatic or C3-C8 heterocyclic group are selected from halogen, C1-10 alkyl, halogenated C1-10 alkyl, C1-10 alkoxy, hydroxy, cyano, nitro, amino or aromatic groups; m is any positive integer from 3 to 5000, n is any positive integer from 3 to 5000, h is any positive integer from 1 to 20, and z is any positive integer from 1 to 5; preferably, z is 1 or 2; the heteroatom in the C3-C8 heterocyclic group is selected from oxygen, sulfur or nitrogen.
[0009] Preferably, the Si-O-Si skeleton bridged multi-nuclear boron catalyst has the following structure:
[0010]
[0011]
[0012] m is any positive integer between 3 and 5000, and n is any positive integer between 3 and 5000.
[0013] In a second aspect, the present invention provides a method for preparing the Si-O-Si skeleton bridged multi-nuclear boron catalyst according to the first aspect of the present invention, comprising the following steps:
[0014] An organic solvent is added to a Si-O-Si precursor compound containing vinyl, and then a borohydride reagent HBY2 is added dropwise. The reaction is heated at 25-80°C for 10-30 hours, and the reaction mixture is concentrated in vacuo to obtain a crude product. The crude product is washed with a solvent for 2-5 times for purification, and then vacuum dried at room temperature for 10-20 hours to obtain a Si-O-Si skeleton-bridged multi-nuclear boron catalyst.
[0015] Among them, the Si-O-Si precursor compound containing vinyl is preferably:
[0016]
[0017] R 1、 The limitations of n, m, h, and z are the same as those described above.
[0018] Wherein, the borohydride reagent is selected from one or more of 9-borabicyclo[3.3.1]nonane, cyclopentaborane, cyclohexaborane, dicyclohexylborane, diphenylborane or 3-methylcyclopentaborane; the molar ratio of the vinyl-containing Si-O-Si precursor compound to the borohydride reagent is 1:3-5000, the organic solvent is selected from one or more of tetrahydrofuran, dichloromethane, chloroform, and toluene; and the washing solvent is selected from one or more of pentane, hexane, and petroleum ether.
[0019] The present invention provides, in a third aspect, the use of the Si-O-Si skeleton bridged multinuclear boron catalyst of the first aspect of the present invention. On the one hand, the Si-O-Si skeleton bridged multinuclear boron catalyst can be used to catalyze polymerization to prepare a polymer, wherein the polymerization reaction is ring-opening polymerization or copolymerization, and the prepared polymer includes polyether, polyester or polycarbonate, wherein the homopolymerization of epoxy monomer is catalyzed to obtain polyether, the polymerization of epoxy monomer and carbon dioxide is catalyzed to obtain polycarbonate, and the polymerization of epoxy monomer and cyclic acid anhydride is catalyzed to obtain polyester. On the other hand, the Si-O-Si skeleton bridged multinuclear boron catalyst can be used to catalyze the coupling of epoxy monomer and carbon dioxide to prepare cyclic carbonate organic small molecules.
[0020] Wherein, the epoxy monomer in the above catalytic reaction includes but is not limited to the following structures:
[0021]
[0022]
[0023]
[0024] Furthermore, the method for obtaining polyether by homopolymerizing epoxy monomers catalyzed by Si-O-Si skeleton bridged multinuclear boron catalyst is to optionally construct a binary catalyst system with the Si-O-Si skeleton bridged multinuclear boron catalyst and an initiator, wherein the initiator is an onium salt, an organic base, and an active proton species, and the binary catalyst system is applied to the polymerization of epoxy monomers with or without chain transfer to obtain the reaction of the polyether. Specifically, the method comprises the following steps:
[0025] In a glove box, weigh a suitable binary catalyst system, epoxy monomer, and chain transfer agent and place them in a dry pressure-resistant bottle equipped with a magnet. Seal the pressure-resistant bottle and take it out. Control the reaction temperature at -20 to 45°C and the reaction time at 1 to 120 minutes to obtain a polyether. The molar ratio of epoxy monomer, Si-O-Si skeleton bridged multi-nuclear boron catalyst, and initiator is 200-30000:1:0.125-0.5, and the amount of chain transfer agent is 0-1000 molar equivalent of Si-O-Si skeleton bridged multi-nuclear boron catalyst. The molecular weight of the obtained polyether is in the range of 100 to 1079300 g / mol, and the molecular weight distribution is In the range of 1.03 to 1.17.
[0026] Wherein, the initiator onium salt is selected from tetrabutylammonium chloride, tetrabutylammonium succinate, One or more of BrPPh4, BrPPh3nBu, BrPPh3Me.
[0027] Wherein, the initiator organic base is selected from triethylamine NEt3, N,N,N',N'-tetraethylethylenediamine, (DMAP), (DBU), (TBD), (Me-TBD), One or more of .
[0028] Wherein, the active proton species is G-OH, G is H, an optionally substituted C1-10 alkyl, an optionally substituted aryl, and the substituent is selected from azide, olefin, alkyne, nitro, ester, amide, amine, and carboxylic acid.
[0029] Wherein, the chain transfer agent is selected from H2O,
[0030]
[0031] One or more of .
[0032] Among them, the epoxy monomer is as mentioned above, preferably propylene oxide or ethylene oxide.
[0033] Among them, the Si-O-Si skeleton bridged multi-nuclear boron catalyst is as mentioned above, preferably CAT13, CAT8 or CAT1.
[0034] Wherein, the molar ratio of the epoxy monomer, the Si-O-Si skeleton bridged multi-nuclear boron catalyst and the initiator is 200-30000:1:0.125-0.5, preferably 200:1:0.5, 1000:1:0.5, 3000:1:0.5, 5000:1:5, 10000:1:100 or 30000:1:1000.
[0035] The amount of the chain transfer agent used is 0-1000 molar equivalents of the Si-O-Si skeleton bridged multi-nuclear boron catalyst, preferably 10, 100, 500 or 1000 molar equivalents.
[0036] The reaction temperature is -20 to 45° C., preferably -20° C., 0° C., 25° C. or 45° C. The reaction time is 1 to 120 min, preferably 5 min, 10 min, 30 min, 60 min or 120 min.
[0037] Furthermore, a catalytic method for obtaining polycarbonate by catalyzing the polymerization of epoxy monomer and carbon dioxide by Si-O-Si skeleton bridged multinuclear boron catalyst comprises the following steps: in a glove box, weighing a suitable Si-O-Si skeleton bridged multinuclear boron catalyst, an initiator, and an epoxy monomer and placing them in a dry reactor equipped with a magnet, sealing the reactor and taking it out, filling it with CO2, controlling the pressure at 1.5 to 2.5 MPa, the reaction temperature at 40 to 80°C, and the reaction time at 1.25 to 12 hours to obtain polycarbonate. The molecular weight of the obtained polycarbonate is in the range of 100 to 100,000 g / mol, and the molecular weight distribution is In the range of 1.10 to 1.30.
[0038] The epoxy monomer is as mentioned above, preferably propylene oxide PO or ethylene oxide EO.
[0039] Among them, the Si-O-Si skeleton bridged multi-nuclear boron catalyst is as mentioned above, preferably CAT13 or CAT1.
[0040] Among them, the initiator is as mentioned above, and is preferably an organic base.
[0041] The molar ratio of epoxy monomer, Si-O-Si skeleton bridged multi-nuclear boron catalyst and initiator is 500-100000:1:1-0.01, preferably 500:1:0.01, 2500:1:0.5, 5000:1:0.2 or 100000:1:1.
[0042] Wherein, a chain transfer agent may be optionally added to the above reaction, and its amount is 0-1000 molar equivalents of the Si-O-Si skeleton bridged multi-nuclear boron catalyst, preferably 10, 100, 500 or 1000 molar equivalents.
[0043] Wherein, the reaction pressure is 1.5-2.5 MPa, preferably 1.5 MPa, 2 MPa, 2.2 MPa or 2.5 MPa; the reaction temperature is 25-80°C, preferably 25°C, 50°C, 60°C, 70°C or 80°C; the reaction time is 0.05-48h, preferably 0.05h, 1h, 2h, 5h, 7h, 12h, 24h or 48h.
[0044] Further, a catalytic method for obtaining polyester by catalyzing the polymerization of epoxy monomer and cyclic anhydride by Si-O-Si skeleton bridged multi-nuclear boron catalyst comprises the following steps: in a glove box, weighing appropriate epoxy monomer, cyclic anhydride, Si-O-Si skeleton bridged multi-nuclear boron catalyst and initiator and placing them in a dry pressure-resistant bottle equipped with a magnet, sealing the pressure-resistant bottle and taking it out, controlling the reaction temperature at 60-130°C, and the reaction time at 0.25-15h to obtain polyester. The molecular weight of the obtained polyester is in the range of 20700-59400 g / mol, and the molecular weight distribution is In the range of 1.18 to 1.21.
[0045] Among them, the epoxy monomer is as described above, preferably cyclohexene oxide (epoxycyclohexene) (C6H 10 O, abbreviated as CHO) or propylene oxide.
[0046] Among them, the Si-O-Si skeleton bridged multi-nuclear boron catalyst is as mentioned above, preferably CAT8, CAT13 or CAT1.
[0047] Among them, the cyclic acid anhydride is preferably phthalic anhydride, succinic anhydride, and maleic anhydride.
[0048] Among them, the initiator is as described above, preferably an onium salt or an organic base.
[0049] The molar ratio of epoxy monomer, cyclic anhydride, Si-O-Si skeleton bridged multi-nuclear boron catalyst and initiator is 400-10000:200-500:2:1, preferably 400:200:2:1 or 10000:5000:2:1.
[0050] Wherein, a chain transfer agent may be optionally added to the above reaction, and its amount is 0-1000 molar equivalents of the Si-O-Si skeleton bridged multi-nuclear boron catalyst, preferably 10, 100, 500 or 1000 molar equivalents.
[0051] Wherein, the reaction temperature is 60-130°C, preferably 60°C, 80°C, 90°C, 100°C, 120°C or 130°C; the reaction time is 0.25-0.75h, preferably 0.25h, 0.3h, 0.4h, 0.5h, 0.6h or 0.75h.
[0052] Beneficial Effects of the Invention
[0053] (1) The Si-O-Si skeleton bridged multi-nuclear boron catalyst provided by the present invention has the advantages of high activity, simple preparation method, low cost, etc. This type of catalyst can regulate the type of polymerization substrate and polymer by regulating the reaction conditions, catalytic system, substrate, etc. Due to the synergistic effect of the multi-boron center, polyethers, polyesters, polycarbonates and other polymers can be efficiently prepared, which greatly expands the types of boron catalysts and polymers.
[0054] (2) The Si-O-Si skeleton bridged multi-nuclear boron catalyst provided by the present invention has good water and oxygen resistance and can tolerate acid as a chain transfer agent to prepare polyethers, polyesters, and polycarbonates containing carboxylic acid groups.
[0055] (3) The Si-O-Si skeleton bridged multi-nuclear boron catalyst provided by the present invention not only improves the efficiency and selectivity of ring-opening polymerization and copolymerization reactions, but also has good environmental friendliness and application prospects, and is suitable for industrial large-scale production of high-performance polymer materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:
[0057] Figure 1 Based on Si-O-Si framework bridged multi-nuclear boron catalyst CAT7 1 H NMR.
[0058] Figure 2 Based on Si-O-Si framework bridged multi-nuclear boron catalyst CAT7 11 B NMR.
[0059] Figure 3 Based on Si-O-Si framework bridged multi-nuclear boron catalyst CAT8 1 H NMR.
[0060] Figure 4 Based on Si-O-Si framework bridged multi-nuclear boron catalyst CAT8 11 B NMR.
[0061] Figure 5 Based on Si-O-Si framework bridged multinuclear boron catalyst CAT13 1 H NMR.
[0062] Figure 6 Based on Si-O-Si framework bridged multinuclear boron catalyst CAT13 11 B NMR.
[0063] Figure 7 This is the water and oxygen resistance diagram of Si-O-Si skeleton-bridged multi-nuclear boron catalyst CAT13. DETAILED DESCRIPTION
[0064] The Si-O-Si skeleton bridged multi-nuclear boron catalyst and its application provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0065] Example 1: Preparation of Catalyst CAT8
[0066] The catalyst CAT8 precursor and 9-boranebicyclo[3.3.1]nonane (9-BBN) were selected to prepare Si-O-Si skeleton bridged multi-nuclear boron catalyst, and the specific operation was as follows:
[0067] In the glove box, the catalyst CAT8 precursor tetramethyltetravinylcyclotetrasiloxane (1000mg, 2.9mmol) (vinyl content 11.6mmol, 1 molar equivalent) was added to a pre-dried solvent storage bottle equipped with a stirring magnet, tetrahydrofuran (10mL) was added, and then 9-boranebicyclo [3.3.1] nonane (9-BBN) (0.5M inTHF) (23.5mL, 11.75mmol, 4.05 molar equivalent) was added dropwise and heated at 60°C for 48h. The reaction mixture was concentrated in vacuo to obtain a crude solid product, which was further purified by washing three times with pentane. The white solid product was dried in vacuo at room temperature for 12h. Yield 99%.
[0068] Example 2: Preparation of Catalyst CAT1 Precursor
[0069] Octamethylcyclotetrasiloxane (52.3mL, 168.5mmol), tetramethyltetravinylcyclotetrasiloxane (58.8mL, 168.5mmol) and end-capping agent tetramethyldivinyldisiloxane (58.8mL, 168.5mmol, CAS No.: 2627-95-4) were mixed together, and finally phosphazene base catalyst CTPB (100mg, 30.3mmol) was added, and heated at 100℃ for 4h. When the viscosity of the system no longer increased, phosphoric acid was added to terminate the reaction and stirred for 15 minutes. After returning to room temperature, it was allowed to stand, dissolved with an appropriate amount of dichloromethane, and then poured into methanol for precipitation. The precipitated product was dried in a 60℃ oven for 12 hours, and finally dried with a vacuum pump to obtain a pure product.
[0070] Example 3: Preparation of Catalyst CAT1
[0071] The catalyst CAT1 precursor prepared in Example 2 was selected (n and m = 280) and 9-boranobicyclo[3.3.1]nonane (9-BBN) to prepare Si-O-Si skeleton bridged multinuclear boron catalyst, the specific operation is as follows:
[0072] In a glove box, the catalyst CAT1 precursor (1000 mg, 12.5 mmol) (vinyl content 6.25 mmol, 50% molar ratio) was added to a pre-dried solvent storage bottle equipped with a stirring magnet, tetrahydrofuran (10 mL) was added, and then 9-boranebicyclo[3.3.1]nonane (9-BBN) (0.5 M in THF) (16.3 mL, 8.125 mmol) was added dropwise and heated at 60 ° C for 48 h. The reaction mixture was concentrated in vacuo to obtain a crude solid product, which was further purified by washing with pentane three times. The white solid product was dried in vacuo at room temperature for 12 h. The yield was 99%.
[0073] The following is an application example of Si-O-Si skeleton bridged multi-nuclear boron catalyst in polymerization reaction
[0074] Application Example 1-12: Homopolymerization of alkylene oxide (PO) catalyzed by CAT1 and CAT8 / onium salts
[0075]
[0076] In a glove box, PO, catalyst and onium salt are weighed into a 10 mL pressure vial that has been flame dried in advance and equipped with a magnetic stirrer, the vial is sealed and taken out, and the reaction temperature is set to -20 to 45°C, and the molar ratio of PO to catalyst and ammonium salt is 200:1:0.5 to 10000:1:0.5. The specific operations of Application Examples 1 to 12 are as follows, and the key data are summarized in Table 1.
[0077] Application Example 1: In a glove box, add CAT1 (4.4 mg, 0.0142 mmol, 1 molar equivalent), Bu4NCl (2.0 mg, 0.0071 mmol, 0.5 molar equivalent) and PO (0.994 ml, 14.2 mmol, 1000 molar equivalent) to a pre-flamed 10 mL pressure vial equipped with a magnetic stirrer, and react at 25°C for 5 min. After the reaction is completed, quench the reaction, add a small amount of dichloromethane to dilute, and take part of the reaction solution for detection. GPC measured the number average molecular weight M n 16.7kg / mol, molecular weight distribution is 1.14.
[0078] Application Example 2: In a glove box, add CAT1 (22.2 mg, 0.071 mmol, 1 molar equivalent), Bu4NCl (10 mg, 0.036 mmol, 0.5 molar equivalent) and PO (24.8 ml, 355 mmol, 5000 molar equivalent) to a pre-flame dried 50 mL pressure bottle equipped with a magnetic stirrer, and react at 25°C for 60 min. After the reaction is completed, quench the reaction, add a small amount of dichloromethane to dilute, and take part of the reaction solution for detection. GPC measured the number average molecular weight M n 523.8kg / mol, molecular weight distribution is 1.14.
[0079] Application Example 3: In a glove box, add CAT1 (1.1 mg, 0.0036 mmol, 1 molar equivalent), Bu4NCl (0.5 mg, 0.0018 mmol, 0.5 molar equivalent) and PO (2.48 ml, 35.5 mmol, 10000 molar equivalent) to a pre-flame dried 10 mL pressure vial equipped with a magnetic stirrer, and react at 25°C for 8 min. After the reaction is completed, quench the reaction, add a small amount of dichloromethane to dilute, and take part of the reaction solution for detection. GPC measured the number average molecular weight M n 41.7kg / mol, molecular weight distribution is 1.16.
[0080] Application Example 4: In a glove box, CAT1 (0.8 mg, 0.0024 mmol, 1 molar equivalent), Bu4NCl (0.3 mg, 0.0012 mmol, 0.5 molar equivalent) and PO (4.97 ml, 71 mmol, 30000 molar equivalent) were added to a pre-flame dried 10 mL pressure vial equipped with a magnetic stirrer, and the reaction was carried out at 25°C for 10 min. After the reaction was completed, the reaction was quenched, a small amount of dichloromethane was added to dilute, and part of the reaction solution was taken for detection. GPC measured the number average molecular weight M n 98.1kg / mol, molecular weight distribution is 1.15.
[0081] Application Example 5: In a glove box, add CAT1 (2.2 mg, 0.0071 mmol, 1 molar equivalent), ethylene glycol (0.0396 ml, 0.71 mmol, 100 molar equivalent), Bu4NCl (1 mg, 0.0036 mmol, 0.5 molar equivalent) and PO (4.97 ml, 71 mmol, 10000 molar equivalent) to a pre-flame dried 10 mL pressure vial equipped with a magnetic stirrer, and react at 25°C for 12 min. After the reaction is completed, quench the reaction, add a small amount of dichloromethane to dilute, and take part of the reaction solution for detection. GPC measured the number average molecular weight M n 96.3kg / mol, molecular weight distribution is 1.16.
[0082] Application Example 6: In a glove box, add CAT1 (221.8 mg, 0.71 mmol, 1 molar equivalent), tetrabutylammonium succinate (216.4 mg, 0.36 mmol, 0.5 molar equivalent) and PO (49.7 ml, 710 mmol, 1000 molar equivalent) to a 250 mL pressure bottle that has been flame-dried in advance and equipped with a magnetic stirrer, and react at 25°C for 100 min. After the reaction is completed, quench the reaction, add a small amount of dichloromethane to dilute, and take part of the reaction solution for detection. GPC measured the number average molecular weight M n 1080.1kg / mol, molecular weight distribution is 1.16.
[0083] Application Example 7: In a glove box, add CAT1 (22.2 mg, 0.071 mmol, 1 molar equivalent), tetrabutylammonium succinate (21.6 mg, 0.036 mmol, 0.5 molar equivalent) and PO (24.8 ml, 355 mmol, 5000 molar equivalent) to a pre-flame dried 50 mL pressure bottle equipped with a magnetic stirrer, and react at 25°C for 50 min. After the reaction is completed, quench the reaction, add a small amount of dichloromethane to dilute, and take part of the reaction solution for detection. GPC measured the number average molecular weight M n 522.3kg / mol, molecular weight distribution is 1.15.
[0084] Application Example 8: In a glove box, CAT1 (7.2 mg, 0.0213 mmol, 1 molar equivalent), tetrabutylammonium succinate (6.4 mg, 0.0107 mmol, 0.5 molar equivalent) and PO (14.9 ml, 213 mmol, 10000 molar equivalent) were added to a 50 mL pressure bottle that had been flame dried in advance and equipped with a magnetic stirrer. The mixture was reacted at 25°C for 40 min. After the reaction was completed, the reaction was quenched, a small amount of dichloromethane was added for dilution, and part of the reaction solution was taken for detection. The number average molecular weight M was measured by GPC. n 303.5kg / mol, molecular weight distribution is 1.16.
[0085] Application Example 9: In a glove box, CAT1 (7.2 mg, 0.0213 mmol, 1 molar equivalent), tetrabutylammonium benzoate (7.7 mg, 0.0213 mmol, 1 molar equivalent) and PO (14.9 ml, 213 mmol, 10000 molar equivalent) were added to a 50 mL pressure bottle vial that had been flame-dried in advance and equipped with a magnetic stirrer, and the mixture was reacted at 25°C for 380 min. After the reaction was completed, CAT1 was precipitated, and PO (14.9 ml, 213 mmol, 10000 molar equivalent) and tetrabutylammonium benzoate (13.1 mg, 0.036 mmol, 0.5 molar equivalent) were added, and the reaction was continued for 720 min. The catalyst was further precipitated from the generated PPO, and PO (14.9 ml, 213 mmol, 10000 molar equivalent) and tetrabutylammonium benzoate (13.1 mg, 0.036 mmol, 0.5 molar equivalent) were added. The reaction was continued for 1440 min. A portion of the reaction solution was taken for testing. The number average molecular weights measured by GPC were Mn 297.2 kg / mol, Mn 294.8 kg / mol, and M n 292.6kg / mol, molecular weight distribution They are 1.15, 1.15 and 1.19 respectively.
[0086] Application Example 10: In a glove box, CAT1 (2.2 mg, 0.0071 mmol, 1 molar equivalent), ethylene glycol (0.04 mL, 0.71 mmol, 100 molar equivalents), tetrabutylammonium succinate (4.3 mg, 0.0071 mmol, 1 molar equivalent) and PO (4.97 mL, 71 mmol, 10000 molar equivalents) were added to a pre-flame dried 10 mL pressure vial equipped with a magnetic stirrer, and the reaction was carried out at 25°C for 10 min. After the reaction was completed, the reaction was quenched, a small amount of dichloromethane was added for dilution, and part of the reaction solution was taken for detection. The number average molecular weight M was measured by GPC. n 98.4kg / mol, molecular weight distribution is 1.16.
[0087] Application Example 11: In a glove box, CAT8 (59.1 mg, 0.071 mmol, 1 molar equivalent), Bu4NCl (10 mg, 0.036 mmol, 0.5 molar equivalent) and PO (24.8 ml, 355 mmol, 5000 molar equivalent) were added to a 50 mL pressure bottle that had been flame dried in advance and equipped with a magnetic stirrer. The reaction was carried out at 25°C for 70 min. After the reaction was completed, the reaction was quenched, a small amount of dichloromethane was added for dilution, and part of the reaction solution was taken for detection. The number average molecular weight M was measured by GPC. n 21.3kg / mol, molecular weight distribution is 1.15.
[0088] Application Example 12: In a glove box, CAT8 (59.1 mg, 0.071 mmol, 1 molar equivalent), Bu4NCl (10 mg, 0.036 mmol, 0.5 molar equivalent) and PO (49.7 ml, 710 mmol, 10000 molar equivalent) were added to a 50 mL pressure bottle that had been flame dried in advance and equipped with a magnetic stirrer. The reaction was carried out at 25°C for 200 min. After the reaction was completed, the reaction was quenched, a small amount of dichloromethane was added for dilution, and part of the reaction solution was taken for detection. The number average molecular weight M was measured by GPC. n 61.3kg / mol, molecular weight distribution is 1.16.
[0089] Table 1 Summary of key data of application examples 1 to 12.
[0090]
[0091]
[0092] Under the condition of low catalyst loading, it can have high catalytic activity, and polyether polyols with different molecular weights can be obtained by adjusting the chain transfer agent. Among them, when CAT1 is used as a catalyst, under the condition of a monomer / catalyst ratio of 30000 / 1, the conversion rate can reach 96% in 10 minutes of reaction, and the conversion frequency can reach up to 172800h -1 The molecular weight distribution of the polymers obtained by the reaction is below 1.20.
[0093] Application Examples 13-22: Homopolymerization of alkylene oxide (PO) catalyzed by CAT1 / organic base
[0094] In a glove box, PO, catalyst and organic base are weighed into a 10 mL pressure vial that has been flame dried in advance and equipped with a magnetic stirrer, the vial is sealed and taken out, and the reaction temperature is set to -20 to 45°C, the molar ratio of PO to catalyst and organic base is 200:1:0.5 to 10000:1:0.5, and the reaction time is controlled to be 1 to 120 min. The specific operations of Application Examples 13 to 22 are as follows, and the key data are summarized in Table 2.
[0095] Application Example 13: In a glove box, CAT1 (4.4 mg, 0.0142 mmol, 1 molar equivalent), triethylamine (0.7 mg, 0.0071 mmol, 0.5 molar equivalent) and PO (0.994 mL, 14.2 mmol, 1000 molar equivalent) were added to a pre-flame dried 10 mL pressure vial equipped with a magnetic stirrer, and the mixture was reacted at 25°C for 2 min. After the reaction was completed, the reaction was quenched, a small amount of dichloromethane was added for dilution, and part of the reaction solution was taken for detection. The number average molecular weight M was measured by GPC. n 17.2kg / mol, molecular weight distribution is 1.15.
[0096] Application Example 14: In a glove box, CAT1 (22.2 mg, 0.071 mmol, 1 molar equivalent), DBU (0.106 mL, 0.71 mmol, 10 molar equivalents), ethylene glycol (0.396 mL, 7.1 mmol, 100 molar equivalents) and PO (24.8 mL, 355 mmol, 5000 molar equivalents) were added to a pre-flame dried 50 mL pressure bottle equipped with a magnetic stirrer, and the reaction was carried out at 25°C for 40 min. After the reaction was completed, the reaction was quenched, a small amount of dichloromethane was added for dilution, and part of the reaction solution was taken for detection. The number average molecular weight M was measured by GPC. n 520.9 kg / mol, molecular weight distribution is 1.14.
[0097] Application Example 15: In a glove box, CAT1 (1.2 mg, 0.0036 mmol, 1 molar equivalent), DBU (0.0054 mL, 0.036 mmol, 10 molar equivalents), benzoic acid (44 mg, 0.36 mmol, 100 molar equivalents) and PO (2.52 mL, 36 mmol, 10000 molar equivalents) were added to a pre-flame dried 10 mL pressure vial equipped with a magnetic stirrer, and the reaction was carried out at 25°C for 4 min. After the reaction was completed, the reaction was quenched, a small amount of dichloromethane was added for dilution, and part of the reaction solution was taken for detection. The number average molecular weight Mn measured by GPC was 40.9 kg / mol, and the molecular weight distribution was is 1.17.
[0098] Application Example 16: In a glove box, CAT1 (0.8 mg, 0.0024 mmol, 1 molar equivalent), DBU (0.0036 ml, 0.024 mmol, 10 molar equivalents), acetic acid (0.014 ml, 0.24 mmol, 100 molar equivalents) and PO (4.97 ml, 71 mmol, 30000 molar equivalents) were added to a pre-flame dried 10 mL pressure vial equipped with a magnetic stirrer, and the reaction was carried out at 25°C for 9 min. After the reaction was completed, the reaction was quenched, a small amount of dichloromethane was added for dilution, and part of the reaction solution was taken for detection. The number average molecular weight Mn measured by GPC was 99.5 kg / mol, and the molecular weight distribution was is 1.14.
[0099] Application Example 17: In a glove box, add CAT1 (2.2 mg, 0.0071 mmol, 1 molar equivalent), P1 (9.9 mg, 0.036 mmol, 10 molar equivalent), 1,3,5-benzenetricarboxylic acid (149.2 mg, 0.71 mmol, 100 molar equivalent) and PO (4.97 mL, 71 mmol, 10000 molar equivalent) to a pre-flame dried 10 mL pressure vial equipped with a magnetic stirrer, and react at 25°C for 8 min. After the reaction is completed, quench the reaction, add a small amount of dichloromethane to dilute, and take part of the reaction solution for detection. GPC measured the number average molecular weight Mn to be 97.6 kg / mol, and the molecular weight distribution is 1.17.
[0100] Application Example 18: In a glove box, add CAT1 (2.2 mg, 0.0071 mmol, 1 molar equivalent), P2 (92.6 mg, 0.071 mmol, 10 molar equivalents), 1,2,4,5-benzenetetracarboxylic acid (149.2 mg, 0.71 mmol, 100 molar equivalents) and PO (4.97 ml, 71 mmol, 10000 molar equivalents) to a 250 mL pressure bottle that has been flame dried in advance and equipped with a magnetic stirrer, and react at 25°C for 110 min. After the reaction is completed, quench the reaction, add a small amount of dichloromethane to dilute, and take part of the reaction solution for detection. The number average molecular weight Mn measured by GPC is 1079.3 kg / mol, and the molecular weight distribution is is 1.17.
[0101] Application Example 19: In a glove box, CAT1 (1.1 mg, 0.0036 mmol, 1 molar equivalent), P4 (71.1 mg, 0.036 mmol, 10 molar equivalents), benzoic acid (44 mg, 0.36 mmol, 100 molar equivalents) and PO (2.48 mL, 35.5 mmol, 10000 molar equivalents) were added to a pre-flame dried 10 mL pressure vial equipped with a magnetic stirrer, and the reaction was carried out at 25°C for 4 min. After the reaction was completed, the reaction was quenched, a small amount of dichloromethane was added for dilution, and part of the reaction solution was taken for detection. The number average molecular weight Mn measured by GPC was 40.9 kg / mol, and the molecular weight distribution was is 1.17.
[0102] Application Example 20: In a glove box, CAT8 (2.0 mg, 0.0024 mmol, 1 molar equivalent), P1 (5.6 mg, 0.024 mmol, 10 molar equivalents), acetic acid (0.0137 mL, 0.24 mmol, 100 molar equivalents) and PO (4.97 mL, 71 mmol, 30000 molar equivalents) were added to a pre-flame dried 10 mL pressure vial equipped with a magnetic stirrer, and the reaction was carried out at 25°C for 8 min. After the reaction was completed, the reaction was quenched, a small amount of dichloromethane was added for dilution, and part of the reaction solution was taken for detection. The number average molecular weight Mn measured by GPC was 99.5 kg / mol, and the molecular weight distribution was is 1.14.
[0103] Application Example 21: In a glove box, CAT8 (5.9 mg, 0.0071 mmol, 1 molar equivalent), P2 (92.6 mg, 0.071 mmol, 10 molar equivalents), 1,3,5-benzenetricarboxylic acid (149.2 mg, 0.71 mmol, 100 molar equivalents) and PO (4.97 mL, 71 mmol, 10000 molar equivalents) were added to a pre-flame dried 10 mL pressure vial equipped with a magnetic stirrer, and the reaction was carried out at 25°C for 8 min. After the reaction was completed, the reaction was quenched, a small amount of dichloromethane was added for dilution, and part of the reaction solution was taken for detection. The number average molecular weight Mn measured by GPC was 97.6 kg / mol, and the molecular weight distribution was is 1.17.
[0104] Application Example 22: In a glove box, CAT8 (5.9 mg, 0.0071 mmol, 1 molar equivalent), P1 (16.6 mg, 0.071 mmol, 10 molar equivalents), 1,2,4,5-benzenetetracarboxylic acid (180.5 mg, 0.71 mmol, 100 molar equivalents) and PO (4.97 mL, 71 mmol, 10000 molar equivalents), and PO (0.497 mL, 7.1 mmol, 1000 molar equivalents) were added to a 250 mL pressure bottle that had been flame-dried in advance and equipped with a magnetic stirrer. The reaction was carried out at 25°C for 110 min. After the reaction was completed, the reaction was quenched, a small amount of dichloromethane was added for dilution, and part of the reaction solution was taken for detection. The number average molecular weight M was measured by GPC. n 1079.3kg / mol, molecular weight distribution is 1.17.
[0105] Table 2 Summary of key data of application examples 13 to 22.
[0106]
[0107] The system can tolerate acid as a chain transfer agent and has high catalytic activity. Under the conditions of a monomer / catalyst ratio of 30,000 / 1 and the addition of 100 molar equivalents of acetic acid as a chain transfer agent, a conversion rate of 92% can be achieved after 9 minutes of reaction, and the molecular weight distribution of the obtained polymer is below 1.20.
[0108] Application Examples 23-34: Copolymerization of alkylene oxide and CO2 using CAT1
[0109]
[0110] Place a stainless steel back pressure autoclave with a magnetic stirrer in an oven at 110°C, take it out while hot after 2 hours, seal it, evacuate it until the autoclave slowly cools to room temperature, and replace it with nitrogen three times for standby use. Under nitrogen protection, weigh a certain amount of CAT1 in a dry and clean back pressure autoclave, add a certain amount of PO and organic base, stir for 10 minutes until the catalyst is completely dissolved, and then fill the autoclave with a certain pressure of CO2 (1.5-2.5MPa). Set the reaction temperature to -40~80°C, the molar ratio of organic base to catalyst and PO to 5:1:500~10:1:5000, the reaction time is controlled at 0.25h~12h, terminate the reaction, and slowly release the remaining CO2 at room temperature. Take out a very small amount of the reaction product for 'H NMR and GPC analysis. In addition, the system can also add acid as a chain transfer agent to carry out polymerization experiments. The specific operations of Application Examples 23~34 are as follows, and the key data are summarized in Table 3.
[0111] Application Example 23: In a glove box, CAT1 (11.3 mg, 0.036 mmol, 1 molar equivalent), NEt3 (29.1 mg, 0.288 mmol, 8 molar equivalents), and PO (1.26 mL, 18 mmol, 500 molar equivalents) were added to a pre-flamed 10 mL high-pressure reactor equipped with a magnetic stirrer. The reactor was transferred out of the glove box, filled with carbon dioxide at a pressure of 15 bar, and reacted at 60°C for 4 hours. After the reaction was completed, the reaction was quenched and part of the reaction liquid was taken for detection. The number average molecular weight Mn measured by GPC was 50.3 kg / mol, and the molecular weight distribution was is 1.19.
[0112] Application Example 24: In a glove box, CAT1 (11.3 mg, 0.036 mmol, 1 molar equivalent), tetrabutylammonium succinate (173.1 mg, 0.288 mmol, 8 molar equivalents), and PO (2.52 mL, 36 mmol, 1000 molar equivalents) were added to a pre-flamed 10 mL high-pressure reactor equipped with a magnetic stirrer. The reactor was transferred out of the glove box, filled with carbon dioxide at a pressure of 15 bar, and reacted at 60°C for 6 hours. After the reaction was completed, the reaction was quenched and part of the reaction liquid was taken for detection. The number average molecular weight Mn measured by GPC was 112.4 kg / mol, and the molecular weight distribution was is 1.17.
[0113] Application Example 25: In a glove box, CAT1 (11.3 mg, 0.036 mmol, 1 molar equivalent), DBU (0.0269 mL, 0.18 mmol, 5 molar equivalents), ethylene glycol (0.201 mL, 3.6 mmol, 100 molar equivalents) and PO (2.52 mL, 36 mmol, 1000 molar equivalents) were added to a pre-flame dried 10 mL high pressure reactor equipped with a magnetic stirrer. The reactor was transferred out of the glove box, filled with carbon dioxide at a pressure of 15 bar, reacted at 60°C for 5 h, quenched after the reaction, and part of the reaction liquid was taken for detection. The number average molecular weight Mn measured by GPC was 112.5 kg / mol, and the molecular weight distribution was is 1.19.
[0114] Application Example 26: In a glove box, CAT1 (1.1 mg, 0.0036 mmol, 1 molar equivalent), DBU (0.00269 mL, 0.018 mmol, 5 molar equivalents), ethylene glycol (0.0201 mL, 0.36 mmol, 100 molar equivalents) and PO (1.26 ml, 18 mmol, 5000 molar equivalents) were added to a pre-flamed 10 mL high-pressure reactor equipped with a magnetic stirrer. The reactor was transferred out of the glove box, filled with carbon dioxide at a pressure of 25 bar, reacted at 60°C for 2 h, quenched after the reaction, and part of the reaction liquid was taken for detection. The number average molecular weight Mn measured by GPC was 48.6 kg / mol, and the molecular weight distribution was is 1.21.
[0115] Application Example 27: In a glove box, CAT1 (1.1 mg, 0.0036 mmol, 1 molar equivalent), P1 (4.2 mg, 0.018 mmol, 5 molar equivalents), ethylene glycol (0.0201 mL, 0.36 mmol, 100 molar equivalents) and PO (1.26 ml, 18 mmol, 5000 molar equivalents) were added to a pre-flame dried 10 mL high pressure reactor equipped with a magnetic stirrer. The reactor was transferred out of the glove box and filled with carbon dioxide at a pressure of 15 bar. The reaction was carried out at 60°C for 1.5 h. After the reaction was completed, the reaction was quenched and part of the reaction solution was taken for detection. The number average molecular weight Mn measured by GPC was 49.2 kg / mol, and the molecular weight distribution was is 1.20.
[0116] Application Example 28: In a glove box, CAT1 (1.1 mg, 0.0036 mmol, 1 molar equivalent), P2 (6.6 mg, 0.018 mmol, 5 molar equivalents), ethylene glycol (0.0201 mL, 0.36 mmol, 100 molar equivalents) and PO (1.26 ml, 18 mmol, 5000 molar equivalents) were added to a pre-flame dried 10 mL high pressure reactor equipped with a magnetic stirrer. The reactor was transferred out of the glove box, filled with carbon dioxide at a pressure of 15 bar, reacted at 60°C for 3 h, quenched after the reaction, and part of the reaction liquid was taken for detection. The number average molecular weight Mn measured by GPC was 49.3 kg / mol, and the molecular weight distribution was is 1.21.
[0117] Application Example 29: In a glove box, CAT1 (11.3 mg, 0.036 mmol, 1 molar equivalent), P2 (66.1 mg, 0.18 mmol, 5 molar equivalents), acetic acid (0.201 mL, 3.6 mmol, 100 molar equivalents) and PO (2.52 ml, 36 mmol, 1000 molar equivalents) were added to a pre-flamed 10 mL high-pressure reactor equipped with a magnetic stirrer. The reactor was transferred out of the glove box, filled with carbon dioxide at a pressure of 15 bar, and reacted at 60°C for 2 h. After the reaction was completed, the reaction was quenched and part of the reaction liquid was taken for detection. The number average molecular weight Mn measured by GPC was 92.4 kg / mol, and the molecular weight distribution was is 1.18.
[0118] Application Example 30: In a glove box, CAT1 (11.3 mg, 0.036 mmol, 1 molar equivalent), P2 (132.3 mg, 0.36 mmol, 10 molar equivalents), succinic acid (425.1 mg, 3.6 mmol, 100 molar equivalents) and PO (12.6 mL, 180 mmol, 5000 molar equivalents) were added to a pre-flamed 100 mL autoclave equipped with a magnetic stirrer. The autoclave was transferred out of the glove box, filled with carbon dioxide at a pressure of 15 bar, and reacted at 60°C for 15 h. After the reaction was completed, the reaction was quenched and part of the reaction solution was taken for detection. The number average molecular weight Mn measured by GPC was 448.1 kg / mol, and the molecular weight distribution was is 1.19.
[0119] Application Example 31: In a glove box, CAT1 (1.3 mg, 0.0036 mmol, 1 molar equivalent), P2 (13.2 mg, 0.036 mmol, 10 molar equivalents), 1,3,5-benzenetricarboxylic acid (75.7 mg, 0.36 mmol, 100 molar equivalents) and PO (1.26 ml, 18 mmol, 5000 molar equivalents) were added to a pre-flamed 10 mL high-pressure reactor equipped with a magnetic stirrer. The reactor was transferred out of the glove box, filled with carbon dioxide at a pressure of 25 bar, and reacted at 60°C for 4 hours. After the reaction was completed, the reaction was quenched and part of the reaction liquid was taken for detection. The number average molecular weight Mn measured by GPC was 48.7 kg / mol, and the molecular weight distribution was is 1.19.
[0120] Application Example 32: In a glove box, CAT1 (1.3 mg, 0.0036 mmol, 1 molar equivalent), P2 (13.2 mg, 0.036 mmol, 10 molar equivalents), 1,2,4,5-benzenetetracarboxylic acid (91.5 mg, 0.36 mmol, 100 molar equivalents) and PO (1.26 ml, 18 mmol, 5000 molar equivalents) were added to a pre-flamed 10 mL high-pressure reactor equipped with a magnetic stirrer. The reactor was transferred out of the glove box, filled with carbon dioxide at a pressure of 15 bar, and reacted at 60°C for 3 hours. After the reaction was completed, the reaction was quenched and part of the reaction liquid was taken for detection. The number average molecular weight Mn measured by GPC was 49.6 kg / mol, and the molecular weight distribution was is 1.21.
[0121] Application Example 33: In a glove box, CAT1 (0.6 mg, 0.0018 mmol, 1 molar equivalent), P1 (4.2 mg, 0.018 mmol, 10 molar equivalent), 1,3,5-benzenetricarboxylic acid (37.9 mg, 0.18 mmol, 100 molar equivalent) and PO (2.4 ml, 18 mmol, 10000 molar equivalent) were added to a 100 mL high-pressure reactor that had been flame-dried in advance and equipped with a magnetic stirrer. The reactor was transferred out of the glove box, filled with carbon dioxide at a pressure of 15 bar, and reacted at 60°C for 2 hours. After the reaction was completed, the reaction was quenched and part of the reaction liquid was taken for detection. The number average molecular weight Mn measured by GPC was 50.3 kg / mol, and the molecular weight distribution was is 1.18.
[0122] Application Example 34: In a glove box, CAT1 (0.6 mg, 0.0018 mmol, 1 molar equivalent), P1 (4.2 mg, 0.018 mmol, 10 molar equivalent), 1,2,4,5-benzenetetracarboxylic acid (45.8 mg, 0.36 mmol, 100 molar equivalent) and PO (2.4 ml, 18 mmol, 10000 molar equivalent) were added to a pre-flamed 10 mL high-pressure reactor equipped with a magnetic stirrer. The reactor was transferred out of the glove box, filled with carbon dioxide at a pressure of 15 bar, reacted at 60°C for 4 hours, quenched after the reaction, and part of the reaction liquid was taken for detection. The number average molecular weight Mn measured by GPC was 52.4 kg / mol, and the molecular weight distribution was is 1.20.
[0123] Table 3 Summary of key data of application examples 23 to 34.
[0124]
[0125]
[0126] Under the condition of low catalyst loading, it can efficiently catalyze the copolymerization of epoxide and carbon dioxide. By adjusting the chain transfer agent, polycarbonate with different molecular weights can be obtained. Under the condition of monomer / catalyst of 10000 / 1, the conversion rate can reach 96% in 2 hours. The conversion frequency can reach up to 4800h -1 The molecular weight distribution of the obtained polymers is around 1.20.
[0127] Application Examples 35-42: Copolymerization of alkylene oxide and cyclic anhydride catalyzed by CAT1 / initiator
[0128]
[0129] In the glove box, take appropriate amounts of cyclic anhydride, alkylene oxide, ammonium salt and catalyst and place them in a pressure-resistant bottle, set the reaction temperature to 60-130°C, the molar ratio of alkylene oxide, cyclic anhydride, CAT1 and ammonium salt to 400:200:2:1-1000:500:2:1, the reaction time is controlled at 0.25-1.25h, and the reaction solution is tested by nuclear magnetic resonance to characterize the monomer conversion rate and product selectivity. After precipitation from methanol, filtration and drying, the GPC data of the polymer is analyzed. The specific operations of Application Examples 35-42 are as follows, and the key data are summarized in Table 4.
[0130] Application Example 35: In a glove box, CAT1 (3.1 mg, 0.01 mmol, 1 molar equivalent), Bu4NCl (2.8 mg, 0.01 mmol, 1 molar equivalent), phthalic anhydride PA (296 mg, 2 mmol, 200 molar equivalents) and cyclohexene oxide CHO (0.4 ml, 4 mmol, 400 molar equivalents) were added in sequence to a 10 mL pressure bottle that had been flame-dried in advance and equipped with a magnetic stirrer. The pressure bottle was transferred out of the glove box and reacted at 60°C for 1 h. After the reaction was completed, the reaction was quenched. After the polymer was purified, the number average molecular weight Mn was measured by GPC to be 23.1 kg / mol, and the molecular weight distribution was is 1.19.
[0131] Application Example 36: In a glove box, CAT1 (3.1 mg, 0.01 mmol, 1 molar equivalent), tetrabutylammonium succinate (6 mg, 0.01 mmol, 1 molar equivalent), phthalic anhydride PA (296 mg, 2 mmol, 200 molar equivalents) and cyclohexene oxide CHO (0.4 ml, 4 mmol, 400 molar equivalents) were added in sequence to a 10 mL pressure bottle that had been flame-dried in advance and equipped with a magnetic stirrer. The pressure bottle was transferred out of the glove box and reacted at 130°C for 0.75 h. After the reaction was completed, the reaction was quenched. After the polymer was purified, the number average molecular weight Mn was measured by GPC to be 25.2 kg / mol, and the molecular weight distribution was is 1.21.
[0132] Application Example 37: In a glove box, CAT1 (22.5 mg, 0.072 mmol, 1 molar equivalent), tetrabutylammonium succinate (42.3 mg, 0.072 mmol, 1 molar equivalent), phthalic anhydride PA (5.3 g, 36 mmol, 500 molar equivalent) and propylene oxide PO (5 mL, 72 mmol, 1000 molar equivalent) were added in sequence to a 50 mL pressure bottle that had been flame-dried in advance and equipped with a magnetic stirrer. The pressure bottle was transferred out of the glove box and reacted at 130° C. for 1.25 h. After the reaction was completed, the reaction was quenched. After the polymer was purified, the number average molecular weight Mn was measured by GPC to be 60.3 kg / mol, and the molecular weight distribution was is 1.21.
[0133] Application Example 38: In a glove box, CAT1 (3.1 mg, 0.01 mmol, 1 molar equivalent), tetrabutylammonium succinate (6 mg, 0.01 mmol, 1 molar equivalent), maleic anhydride (maleic anhydride, MA) (196.1 mg, 2 mmol, 200 molar equivalents) and propylene oxide PO (0.28 mL, 4 mmol, 400 molar equivalents) were added in sequence to a 10 mL pressure bottle that had been flame-dried in advance and equipped with a magnetic stirrer. The pressure bottle was transferred out of the glove box and reacted at 130° C. for 0.75 h. After the reaction was completed, the reaction was quenched. After the polymer was purified, the number average molecular weight Mn was measured by GPC to be 54.8 kg / mol, and the molecular weight distribution was is 1.20.
[0134] Application Example 39: In a glove box, CAT1 (3.1 mg, 0.01 mmol, 1 molar equivalent), tetrabutylammonium succinate (6 mg, 0.01 mmol, 1 molar equivalent), succinic anhydride SA (200 mg, 2 mmol, 200 molar equivalents) and propylene oxide PO (0.28 ml, 4 mmol, 400 molar equivalents) were added in sequence to a 10 mL pressure bottle that had been flame-dried in advance and equipped with a magnetic stirrer. The pressure bottle was transferred out of the glove box and reacted at 60°C for 0.5 h. After the reaction was completed, the reaction was quenched. After the polymer was purified, the number average molecular weight Mn was measured by GPC to be 22.7 kg / mol, and the molecular weight distribution was is 1.21.
[0135] Application Example 40: In a glove box, CAT1 (22.5 mg, 0.072 mmol, 1 molar equivalent), P1 (168.7 mg, 0.72 mmol, 10 molar equivalents), phthalic anhydride PA (5.3 g, 36 mmol, 500 molar equivalents) and propylene oxide PO (5 mL, 72 mmol, 1000 molar equivalents) were added in sequence to a 50 mL pressure bottle that had been flame-dried in advance and equipped with a magnetic stirrer. The pressure bottle was transferred out of the glove box and reacted at 100°C for 0.75 h. After the reaction was completed, the reaction was quenched. After the polymer was purified, the number average molecular weight Mn was measured by GPC to be 24.6 kg / mol, and the molecular weight distribution was is 1.19.
[0136] Application Example 41: In a glove box, CAT1 (22.5 mg, 0.072 mmol, 1 molar equivalent), P1 (168.7 mg, 0.72 mmol, 10 molar equivalents), ethylene glycol (0.402 mL, 7.2 mmol, 100 molar equivalents), maleic anhydride MA (3.6 g, 36 mmol, 500 molar equivalents) and propylene oxide PO (5 mL, 72 mmol, 1000 molar equivalents) were added in sequence to a 10 mL pressure bottle that had been flame-dried in advance and equipped with a magnetic stirrer. The pressure bottle was transferred out of the glove box and reacted at 130° C. for 0.75 h. After the reaction was completed, the reaction was quenched. After the polymer was purified, the number average molecular weight Mn was measured by GPC to be 27.4 kg / mol, and the molecular weight distribution was 2. is 1.21.
[0137] Application Example 42: In a glove box, CAT1 (22.5 mg, 0.072 mmol, 1 molar equivalent), P2 (264.6 mg, 0.72 mmol, 10 molar equivalents), ethylene glycol (0.402 mL, 7.2 mmol, 100 molar equivalents), maleic anhydride MA (3.5 g, 36 mmol, 500 molar equivalents) and propylene oxide PO (5 mL, 72 mmol, 1000 molar equivalents) were added in sequence to a 10 mL pressure bottle that had been flame-dried in advance and equipped with a magnetic stirrer. The pressure bottle was transferred out of the glove box, and the reaction was carried out at 100° C. for 0.25 h. After the reaction was completed, the reaction was quenched. After the polymer was purified, the number average molecular weight Mn measured by GPC was 24.9 kg / mol, and the molecular weight distribution was is 1.18.
[0138] Table 4 Summary of key data of application examples 35 to 42.
[0139]
[0140] The efficient copolymerization of epoxy and anhydride can be achieved at a lower catalyst loading, where under the conditions of epoxy monomer / anhydride / catalyst of 1000 / 500 / 1, a conversion rate of 96% can be achieved after 0.25h of reaction. The highest conversion frequency can reach 3840h -1 , and the molecular weight distribution of the prepared polymers is around 1.20.
[0141] The above is only a preferred embodiment of the present invention. It should be pointed out that although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that several improvements and modifications may be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention and do not deviate from the scope defined by the claims of the present invention.
Claims
1. A Si-O-Si framework-bridged multi-nuclear boron catalyst, characterized in that: Its structure is as follows: Wherein, BY2 is independently selected from optionally substituted R1 is independently selected from hydrogen, halogen, optionally substituted straight or branched C1-8 alkyl, C1-8 alkoxy, C1-C8 alkenyl, C1-C8 alkynyl, optionally substituted aromatic, fused aromatic or C3-C8 heterocyclic; wherein the substituent is selected from halogen, C1-10 alkyl, halogenated C1-10 alkyl, C1-10 alkoxy, hydroxy, cyano, nitro, amino or aromatic; the heteroatom in the C3-C8 heterocyclic group is selected from oxygen, sulfur or nitrogen; m is any positive integer between 3 and 5000, n is any positive integer between 3 and 5000, h is any positive integer between 1 and 20, and z is any positive integer between 1 and 5.
2. The Si-O-Si skeleton-bridged multi-nuclear boron catalyst according to claim 1, characterized in that: The Si-O-Si skeleton-bridged multi-nuclear boron catalyst is: m is any positive integer between 3 and 5000, and n is any positive integer between 3 and 5000.
3. The method for preparing a Si-O-Si skeleton-bridged multi-nuclear boron catalyst according to claim 1 or 2, characterized in that: The following steps are involved: An organic solvent is added to a Si-O-Si precursor compound containing vinyl, and then a borohydride reagent HBY2 is added dropwise. The reaction is heated at 25-80°C for 10-30 hours, and the reaction mixture is concentrated in vacuo to obtain a crude product. The crude product is washed with a solvent for 2-5 times for purification, and then vacuum dried at room temperature for 10-20 hours to obtain a Si-O-Si skeleton-bridged multi-nuclear boron catalyst.
4. The preparation method according to claim 3, characterized in that: The Si-O-Si precursor compound containing vinyl groups is preferably: R 1、 The limitations of n, m, h, and z are the same as those in claim 1 or 2.
5. The preparation method according to claim 3 or 4, characterized in that: The borohydride reagent is selected from one or more of 9-borabicyclo[3.3.1]nonane, cyclopentaborane, cyclohexaborane, dicyclohexylborane, diphenylborane or 3-methylcyclopentaborane; the molar ratio of the vinyl-containing Si-O-Si precursor compound to the borohydride reagent is 1:3-5000, the organic solvent is selected from one or more of tetrahydrofuran, dichloromethane, chloroform and toluene; the washing solvent is selected from one or more of pentane, hexane and petroleum ether.
6. The use of the Si-O-Si skeleton bridged multi-nuclear boron catalyst according to claim 1 or 2, characterized in that: The application is: the Si-O-Si skeleton-bridged multi-nuclear boron catalyst is used to catalyze ring-opening polymerization or copolymerization to prepare polyether polymers, polyester polymers or polycarbonate polymers, or the application is: the Si-O-Si skeleton-bridged multi-nuclear boron catalyst is used to catalyze the coupling of epoxy monomers and carbon dioxide to prepare cyclic carbonate organic small molecules.
7. The use according to claim 6, characterized in that The method for preparing a polyether polymer by using a Si-O-Si skeleton bridged multi-nuclear boron catalyst to catalyze a ring-opening polymerization reaction or a copolymerization polymerization reaction comprises the following steps: constructing a binary catalyst system by using the Si-O-Si skeleton bridged multi-nuclear boron catalyst and an initiator, mixing an appropriate amount of the binary catalyst system, an epoxy monomer, and a chain transfer agent as required in a dry pressure-resistant bottle equipped with a magnet, sealing the pressure-resistant bottle and then taking it out, controlling the reaction temperature at -20 to 45°C, and controlling the reaction time at 1 to 120 minutes, to obtain a polyether polymer.
8. The use according to claim 6, characterized in that The method for preparing a polyester polymer by using a Si-O-Si skeleton bridged multi-nuclear boron catalyst to catalyze a ring-opening polymerization reaction or a copolymerization polymerization reaction comprises the following steps: placing an appropriate amount of epoxy monomer, a cyclic acid anhydride, a Si-O-Si skeleton bridged multi-nuclear boron catalyst and an initiator in a dry pressure-resistant bottle equipped with a magnet, sealing the pressure-resistant bottle and then taking it out, controlling the reaction temperature at 60 to 130° C., and controlling the reaction time at 0.25 to 15 hours, to obtain a polyester polymer.
9. The use according to claim 6, characterized in that The method for preparing a polycarbonate polymer by using a Si-O-Si skeleton bridged multi-nuclear boron catalyst to catalyze a ring-opening polymerization reaction or a copolymerization polymerization reaction comprises the following steps: placing an appropriate amount of a Si-O-Si skeleton bridged multi-nuclear boron catalyst, an initiator, and an epoxy monomer in a dry reaction kettle equipped with a magnet, sealing the reaction kettle and taking it out, filling it with CO2, controlling the pressure at 1.5 to 2.5 MPa, the reaction temperature at 40 to 80° C., and the reaction time at 1.25 to 12 hours to obtain a polycarbonate polymer.
10. The use according to any one of claims 7 to 9, characterized in that: The initiator is an onium salt, an active proton species or an organic base, wherein the onium salt is selected from tetrabutylammonium chloride, tetrabutylammonium succinate, One or more of BrPPh4, BrPPh3nBu, BrPPh3Me; the organic base is selected from triethylamine (NEt3) 、 N,N,N',N'-Tetraethylethylenediamine, One or more of; the active proton species is G-OH, G is H or an optionally substituted C1-10 alkyl or an optionally substituted aryl, and the substituent is selected from azide, olefin, alkyne, nitro, ester, amide, amine or carboxylic acid.
Citation Information
Cited By
Novel diallyl-terminated polyether as well as synthesis method and application thereof
CN120965986A